Clinician and patient readiness to engage with community health workers at epilepsy care centers - Chu, Felicia C.; Jobst, Barbara C.; Murray, Anna; Dawson, Trina; Frisard, Christine F.; Glidden, Barbara; Kaden, Sarah J.; Kiriakopoulos, Elaine T. (Frontiers in Neurology, 2025)
IntroductionFor patients with epilepsy, medical and social support care gaps may potentially be addressed by clinic-based community health workers (CHWs), particularly for patients most susceptible to health disparities. However, little is known of health professionals’ readiness to integrate CHWs into epilepsy health care delivery.MethodsAn online digital survey was developed and distributed to physicians, nurses and social workers working in 12 comprehensive epilepsy centers in the New England region. Questions in the survey pertained to respondents’ perceptions of working with and addressing clinic needs via a CHW at an epilepsy center. Demographic data were also collected.ResultsSurvey results across physicians, nurses and social workers (n = 65) revealed low knowledge and experience with CHWs. Epilepsy clinicians are unaware of the scientific evidence showing positive effects of CHW health outcomes. Knowledge of CHW recruitment, training and supervision is low. Despite this, the data collected demonstrate that social determinants of health care gaps exist for epilepsy patients receiving care at epilepsy centers. These gaps could potentially be addressed by a nontraditional healthcare professional, such as a CHW, instead of a social worker or nurse, thus alleviating burden from advanced practice provider members to address other clinically based patient needs.ConclusionDespite limited understanding of CHW roles or firsthand experience with CHWs, clinician and patient readiness for integration of CHW was high, with a strong indication that clinicians would refer patients to a CHW and that patients felt the potential for health benefit if provided with assistance from a CHW.